Appendix 3.1: Of Trickery and Omissions: Bongbong Marcos Biography from His Official Website - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Recovered via the Internet Archive’s Wayback Machine, these short biographical pieces naturally paint a positive picture of Bongbong Marcos, then a declared candidate for the senate. It tries to focus voters’ attention on Marcos’s post-EDSA track record. Excluded from this narrative are his appointments as Presidential Special Assistant (1978), chairman of the board of the Philippine Communications Satellite Corporation (1985), and governor of Ilocos Norte (1983–1986). The online biography also claims that Marcos received a political science, philosophy, and economics bachelor’s degree from Oxford University, when, as was known both to the US embassy, the media, and some members of the opposition (see appendix 3.6), he actually received a “Special Diploma in Social Studies.” That he does not have a bachelor’s degree also raises questions about how he was admitted to the Wharton School of Business’s master of business administration program, which he also did not complete. Lastly, no mention is made of his first failed run for the senate in 1995; it would appear, based on the online narrative, that he had never lost an election.